2014
DOI: 10.2147/jhc.s48763
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of dual antiplatelet therapy in the prevention of hepatitis B virus-associated hepatocellular carcinoma

Abstract: Platelets, the chief effectors of vascular homeostasis, have been identified as important players in the pathogenesis of both acute and chronic liver disease in preclinical models of hepatitis B viral infection. Platelets are thought to promote the accumulation of virus-specific T-cells into the liver parenchyma. Importantly, the inhibition of platelet activation by clinically relevant doses of aspirin and clopidogrel was able to reduce immune-mediated necroinflammatory liver disease, extracellular matrix depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Preclinical experiments also demonstrated the vital role of platelet activation in pathogenesis of hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) as well as the anticancer effectiveness of dual platelet inhibitors (aspirin plus clopidogrel) [ 87 , 90 ]. Platelet activation in HBV-HCC mouse models led to accumulation of virus-specific CD8 T cells and virus-non-specific inflammatory cells in the liver, increased hepatocellular proliferation, liver fibrosis, and hepatocarcinogenesis.…”
Section: Platelet-associated Molecules and Therapymentioning
confidence: 99%
“…Preclinical experiments also demonstrated the vital role of platelet activation in pathogenesis of hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) as well as the anticancer effectiveness of dual platelet inhibitors (aspirin plus clopidogrel) [ 87 , 90 ]. Platelet activation in HBV-HCC mouse models led to accumulation of virus-specific CD8 T cells and virus-non-specific inflammatory cells in the liver, increased hepatocellular proliferation, liver fibrosis, and hepatocarcinogenesis.…”
Section: Platelet-associated Molecules and Therapymentioning
confidence: 99%
“…In recent years, a growing interest focused on the possible role of APT in preventing HCC, and several studies based on animal models and cell lines were published with the intent to clarify the molecular mechanisms connecting APT with the development of HCC. Sitia et al investigated the effect of low‐dose dual APT (aspirin + clopidogrel) in an HBV‐positive transgenic mice model, observing a reduction of the intrahepatic HBV‐specific CD8+ T‐cells, a decrease in the severity of liver fibrosis and a reduced incidence of HCC 8,37,38 . In this model, the anti‐cancer effect was explained by reducing immune‐mediated chronic liver injury 1,8 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, sorafenib is an anti-PDGFR, VEGFR and EGFR agent, while regorafenib is an anti-EGFR and anti-VEGFR drug, and lenvatinib acts as an anti-VEGFR. 3 In recent years, a growing interest focused on the possible role of APT in preventing HCC, and several studies 8,37,38 In this model, the anti-cancer effect was explained by reducing immunemediated chronic liver injury. 1,8 Zhang et al demonstrated in a murine model, an increased binding between platelets and poorly differentiated HCC, and the administration of clopidogrel triggered tumour cell differentiation and inhibited tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 In this tumor matrix interaction microenvironment, platelet-derived factors directly affect tumor cell proliferation, fibrinogen signaling and immune cell recruitment, and contribute to more invasive and metastatic role in liver cancer. [60][61][62] In addition, VWF is present in ECs and subendothelium, participating and implicating in the pathophysiological processes of HCC. Similarly, VWF deficiency induces survival of tumor cell in lung and results in more metastasis nodules.…”
Section: Function Of Vwf In Tumorigenesis In Hcc Invasion and Metastasismentioning
confidence: 99%
“…Regulation Da et al 24 Tumorigenesis Haibe et al 26 Hilmi et al 27 Thomas et al 30 Invasion and metastasis Methia et al 35 Hodivala-Dilke 40 Guan et al 41 Felcht et al 42 Villanueva et al 44 Viatour et al 48 Valastyan et al 49 Cross talking RefAravalli et al 50 Terraube et al 52 Shavit et al 53 Zanetto et al 54 Zanetto et al 55 Yun et al 56 Sitia et al 60 Sitia et al 61 Carr et al 62 Oleksowicz et al 63 Mahmoudian-Sani et al 69 Lou et al 70 VWF, Von Willebrand factor; HCC, hepatocellular carcinoma.…”
Section: Description Referencesmentioning
confidence: 99%